A Very Simple Model For Simulating Sugar Beet Yield For Potantial Production - Sharifi, Mohammad Sedghi, Amir Heydari, Abdolghayoum Gholipouri, Rauf Seyed (Journal of Phytology, 2009)
Ã‚Â Sugar beet is one of the most important crops in Iran. The potential yield and its limitations can be estimated using a simple model and long-term weather information. The present study was aimed to develop a very simple model for sugar beet. this model is a dynamic and mechanistic simulation model to simulate sugar beet growth and sugar accumulation for potential production condition. Therefore when the water is not a limiting factor for plant growth, maximizing intercepting solar radiation during growth season has major important. Because in this condition, solar radiation is a limiting factor for plant growth. Therefore selecting suitable planting date is important. Crop simulation models help us to determine planting date and to asses risk production. The model uses a few relationships to define leaf area development as a function of accumulated thermal time units. Biomass accumulation was simulated as a function of fraction of photosynthetically active radiation interception and radiation use efficiency. The growth of root is dependent on the biomass accumulation. The model uses a daily time step and readily available maximum and minimum temperatures and solar radiation. The model was tested for different planting dates at Ardabil in Iran. The model performed satisfactory in predicting the leaf area index and root biomass of sugarbeet as influenced by potential production condition. The simulated average root yield and leaf area index and its range were similar to observed root yield and leaf area index (root mean square error for root yield and leaf area index were equal to 3.97 t ha-1 and 1.3 respectively).